TLR9 Ligand (CpG Oligodeoxynucleotide) Induces CLL B-Cells to Differentiate into CD20+ Antibody-Secreting Cells - Ghamlouch, Hussein; Ouled-Haddou, Hakim; Guyart, Aude; Regnier, Aline; Trudel, Stéphanie; Claisse, Jean-François; Fuentes, Vincent; Royer, Bruno; Marolleau, Jean-Pierre; Gubler, Brigitte (Frontiers in Immunology, 2014)
B-cell chronic lymphocytic leukemia (CLL) is the most frequent adult leukemia in the Western world. It is a heterogeneous disease characterized by clonal proliferation and the accumulation of CD5+ mature B lymphocytes. However, the normal counterpart from which the latter cells arise has not yet been identified. CD27 expression and gene expression profiling data suggest that CLL cells are related to memory B-cells. In vitro, memory B-cells differentiate into plasma cells when stimulated with CpG oligodeoxynucleotide (CpG). The objective of the present study was therefore to investigate the ability of CpG, in the context of CD40 ligation, to induce the differentiation of CLL B-cells into antibody-secreting cells (ASCs). CD20+CD38− CLL B-cells were stimulated with a combination of CpG, CD40 ligand and cytokines (CpG/CD40L/c) in a two-step, seven-day culture system. We found that the CpG/CD40L/c culture system prompted CLL B-cells to differentiate into CD19+CD20+CD27+CD38- ASCs. These cells secreted large amounts of IgM and had the same shape as plasma cells. However, only IgMs secreted by ASCs that had differentiated from unmutated CLL B-cells were poly/autoreactive. Class-switch recombination to IgG and IgA was detected in cells expressing the activation-induced cytidine deaminase gene (AICDA). Although these ASCs expressed high levels of the transcription factors PRDM1 (BLIMP1), IRF4 and XBP1s, they did not downregulate expression of PAX5. Our results suggest that CLL B-cells can differentiate into ASCs, undergo class-switch recombination and produce poly/autoreactive antibodies. Furthermore, our findings may be relevant for (i) identifying the normal counterpart of CLL B-cells and (ii) developing novel treatment strategies in CLL.